Analysis of mandipropamid residual levels through systematic method optimization against the matrix complexity of sesame leaves using HPLC/UVD. (24th November 2015) - Farha, Waziha; Rahman, Md. Musfiqur; Abd El‐Aty, A. M.; Kim, Sung‐Woo; Jung, Da‐I; Im, So Jeong; Choi, Jeong‐Heui; Kabir, Md. Humayun; Lee, Kang‐Bong; Shin, Ho‐Chul; Shim, Jae‐Han
Abstract: An analytical method was developed to detect mandipropamid residues in sesame leaves using high‐performance liquid chromatography–ultraviolet detection. Samples were extracted with acetonitrile and were prepurified using a solid‐phase extraction (SPE) cartridge with an additional dispersive‐SPE (d‐SPE) sorbent application. The method was validated using an external calibration curve prepared using pure solvent. The linearity was excellent with determination coefficient = 1. The limits of detection and quantification were 0.003 and 0.01 mg/kg, respectively. Recoveries at three spiking levels – 0.1, 0.5, and 1.0 mg/kg – were in the range 80.3–90.7% with relative standard deviations <2%. This method was applied to field‐treated samples collected from two different areas, Gwangju and Muan, in the Republic of Korea and the half‐lives were similar, 5.10 and 5.41 days, respectively. The pre‐harvest residue limit was also predicted for both sites. The proposed method is sensitive and able to quantify trace amounts of mandipropamid in leafy vegetables. The combination of SPE and d‐SPE effectively removed the matrix components in sesame leaves. Copyright © 2015 John Wiley & Sons, Ltd.